2019
DOI: 10.5114/wiitm.2019.89609
|View full text |Cite
|
Sign up to set email alerts
|

Is every patient eligible to have an office hysteroscopy? A retrospective analysis of 1301 procedures.

Abstract: Introduction: Hysteroscopy is the gold standard for diagnosis and treatment of uterine pathologies. The office setting seems to be safe, reducing the anesthesia risks and also decreasing the overall costs of the procedure. Recent literature suggests that hysteroscopy performed without anesthesia may not be as painless as it was previously considered. Moreover, not every patient can be referred for a hysteroscopy in an office setting. Aim: To analyze the factors correlated with a successful hysteroscopy in an o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…The reasons for not completing the hysteroscopic procedure with the vaginoscopic approach include pain, anxiety, cervical stenosis, excessive flexion of the cervix, vasovagal reaction, a retroverted uterus and adhesions ( 5 , 7 , 18 ) . Between 83% and 98% of diagnostic procedures can be successfully performed with office hysteroscopy ( 7 , 8 , 13 , 19 , 20 ) . However, there are studies reported that the success of outpatient hysteroscopy varies between 44% and 99.5% ( 21 , 20 , 23 ) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reasons for not completing the hysteroscopic procedure with the vaginoscopic approach include pain, anxiety, cervical stenosis, excessive flexion of the cervix, vasovagal reaction, a retroverted uterus and adhesions ( 5 , 7 , 18 ) . Between 83% and 98% of diagnostic procedures can be successfully performed with office hysteroscopy ( 7 , 8 , 13 , 19 , 20 ) . However, there are studies reported that the success of outpatient hysteroscopy varies between 44% and 99.5% ( 21 , 20 , 23 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Between 83% and 98% of diagnostic procedures can be successfully performed with office hysteroscopy ( 7 , 8 , 13 , 19 , 20 ) . However, there are studies reported that the success of outpatient hysteroscopy varies between 44% and 99.5% ( 21 , 20 , 23 ) . In this study, the failure rate for all outpatient hysteroscopy procedures was 3.6%, which is lower than 10% reported in the previously ( 24 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Thanks to the development of minimally invasive techniques, which allow examining individual body cavities, the cervical canal and the uterine cavity can be viewed using small instruments. The use of mini-hysteroscopy, both in reproductive and in peri-and postmenopausal patients, is currently the "gold standard" due to the short hospital stay, short recovery time, integration of clinical practice with the "see and treat" mode, and reduction in the need for additional interventions, such as the need for general anesthesia and performing the procedure in the operating room [1][2][3][4][5]29,30]. Despite the tremendous advances made in mini-hysteroscopy over the past 20 years, many women still experience discomfort and pain in various stages of this procedure, which is the most common factor for treatment discontinuation [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Different stages of mini-hysteroscopy can result in different unpleasant sensations [38][39][40] and different intensities of pain; for example, women who had previously given birth by natural means usually perceive the passage of the hysteroscope through the cervical canal as less painful and the time of the procedure as shorter [29,41,42] or the pain level reported by them 60 minutes after procedure is lower [43]. Among the pain relief methods worth citing are the results of a randomized clinical trial conducted in 2021 by Gulucu et al [44] in which they compared the severity of pain in two groups of women, depending on the temperature of the distension fluid used in the office hysteroscopy (37 °C vs 25 °C).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of difficulties extracting large tissue fragments, the newly introduced Cryoprobe seems to be the best option. Each of the methods described above has its specific applications, but thanks to their mutual complementation, we are now able to excise almost every lesion from the uterine cavity in an outpatient setting [19].…”
Section: Discussionmentioning
confidence: 99%